1998
DOI: 10.1073/pnas.95.24.14196
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α induces adhesion molecule expression through the sphingosine kinase pathway

Abstract: The signaling pathways that couple tumor necrosis factor-␣ (TNF␣) receptors to functional, especially inf lammatory, responses have remained elusive. We report here that TNF␣ induces endothelial cell activation, as measured by the expression of adhesion protein E-selectin and vascular adhesion molecule-1, through the sphingosine kinase (SKase) signaling pathway. Treatment of human umbilical vein endothelial cells with TNF␣ resulted in a rapid SKase activation and sphingosine 1-phosphate (S1P) generation. S1P, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
401
5
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(431 citation statements)
references
References 36 publications
24
401
5
1
Order By: Relevance
“…A recent report has shown that selective lysosomal permeabilization by TNF in hepatocytes is paralleled by sphingosine-mediated lysosomal permeabilization (42). Inhibition of PI3K may sensitize EC to generate sphingosine either by the activation of sphingomyelinase (43) or by de novo biosynthesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that selective lysosomal permeabilization by TNF in hepatocytes is paralleled by sphingosine-mediated lysosomal permeabilization (42). Inhibition of PI3K may sensitize EC to generate sphingosine either by the activation of sphingomyelinase (43) or by de novo biosynthesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Lysophospholipids increase endothelial cell surface expression of Eselectin and vascular cell adhesion molecule-1 in endothelial cells (13). Lysophospholipids also activate the transcription factor NF-B in endothelial cells, increasing the transcription of E-selectin, intracellular adhesion molecule-1, IL-8, and monocyte chemoattractant protein-1 (13)(14)(15)(16). These findings suggest that S1P may activate the endothelium, triggering endothelial expression of selectins and adhesion molecules, thus initiating vascular inflammation.…”
mentioning
confidence: 91%
“…Therefore, it is reasonable to speculate that the cellular function of vascular endothelial cells may be influenced by platelets through S1P. In endothelial cells, however, only a few studies have been reported on the S1P actions and, furthermore, the site of action of S1P has not yet been characterized [16,25,26].…”
Section: Introductionmentioning
confidence: 99%